The impact of yoga in pregnancy on placental growth factor levels and mean arterial pressure in pre-eclampsia: A randomized controlled trial - Zakkiyatus Zainiyah; Eny Susanti; Novita Wulandari (GarVal Editorial Ltda., 2024)
Context: Pre-eclampsia is a pregnancy-related condition characterized by hypertension, proteinuria, and edema occurring after 20 weeks of pregnancy or during the postpartum period. Several markers are often assessed to determine the suitable option for confirming pre-eclampsia diagnosis, one of which is the examination of placental growth factor (PlGF) as a placental ischemia indicator. Aims: To evaluate the impact of prenatal yoga on PlGF and mean arterial pressure (MAP) levels in pre-eclampsia within the Madura region. Methods: A randomized controlled trial was conducted on fifty subjects that were randomly allocated to the experimental group with pre-post control groups consisting of 50 participants, namely 25 pregnant women with pre-eclampsia and 25 healthy individuals. The selection was conducted based on the following inclusion criteria: belonging to Madura ethnicity spanning three generations, exhibiting pregnancy duration >20 weeks, maternal ages ranging from 20-35 years, pre-pregnancy body mass index (BMI) >25, a history of hypertension, diabetes mellitus (DM), kidney disorders, pre-eclampsia, chronic hypertension, or family history of chronic high blood pressure and pre-eclampsia among those at risk. PlGF levels were estimated using an ELISA kit, while blood pressure was measured with an Omron brand sphygmomanometer. Results: Statistical analysis performed with the Wilcoxon sign test and T-test indicated significant differences (p<0.005) in systolic blood pressure, diastolic blood pressure, and MAP between the groups. Furthermore, a significant difference was observed in PlGF levels before and after engaging in prenatal yoga practice (p<0.05). Conclusions: The results showed that prenatal yoga contributed to the elevation of PlGF levels in women with pre-eclampsia, compared to their healthy counterparts.